THE INFLUENCE OF PROMOTIONS, SERVICE QUALITY AND PRICES ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION IN GENERATION Z (Case Study on Users Gojek in Semarang City) - akim, Johan Rahmat H; Purwanto, Edy (Economics and Business International Conference Proceeding, 2024)
Study This aim For know influence Promotion , Quality Service and Prices for Loyalty Customer Mediated Satisfaction Customer . Population in research This is generation Z users Gojek in the city of Semarang which spans aged 17-25 years . With sample A total of 95 respondents were taken use purposive sampling method . Research methods used​ is method quantitative with technique Data analysis used Path Analysis. On research This data sources used are primary data and secondary data with use help tool data analysis of the Smart PLS 4.0 program. Research result This showing that a) promotion influential to loyalty customers b) quality service No influential to loyalty customer c) price influential to loyalty customer d) satisfaction customer influential significant to loyalty customer e) satisfaction customer capable mediate in a way positive significant between promotion to loyalty customer f) satisfaction customer capable mediate in a way negative No significant between quality service to loyalty customer g) satisfaction customer capable mediate in a way positive significant between price to loyalty customers in generation Z users gojek .